Propuesta de una norma técnica en seguridad y salud ocupacional para trabajos de recolección de residuos sólidos municipales - Vidal Falen, José Luis (2020)
This research work is focused on the diagnosis of the working conditions of municipal solid waste collection workers and the determination of the most important risks during their activity. To determine these, information was collected from the same source of the events, who had as main protagonists the Provincial Municipality of Chiclayo, Provincial Municipality of Ferreñafe, Provincial Municipality of Lambayeque, District Municipality of Illimo and District Municipality of Pacora, belonging to the Department of Lamabayeque; comparing the information, analyzing the results by type of municipality and relating the deficiencies in administrative controls and engineering, and absence of a legal standard. Likewise, the proposal to integrate national and international provisions explicitly that may constitute a technical standard in a consistent manner, under a basis based on the correlational valuation analysis of the problem during municipal solid waste collectors and establishing specific parameters. Finally, the elements to be taken into account are proposed within the proposal of a technical norm in occupational health and safety for municipal solid waste collection works, under the parameters established by INACAL for a Peruvian technical standard.